Produksi dan Penetapan Kadar B-glukan dari Tiga Galur Saccharomyces cerevisiae dalam Media Mengandung Molase - Kusmiati Kusmiati; Swasono R. Tamat; S. Nuswantara; Nita Isnaini (Fakultas Farmasi Universitas Pancasila, 2007)
Beta-glucan extracted from the cell membrane of Saccharomyces cerevisiae has been used as food and medical ingredients. Molase as a waste-product of the cane sugar industry, containing 4-9% of glucose and other nutrients, has been investigated to substitute glucose in the YPG fermentation media of Saccharomyces cerevisiae, and to improve the yield of B-glucan by three strains of Saccharomyces cerevisiae (RTA, RN4, and SC). Beta-glucan and protein concentration were determined by spectrophotometric method at a 490 nm and 750 nm respectively. The results showed that molase can be used as glucose-substitute in the YPG media for the production of B-glucan by three strains of Saccharomyces cerevisiae. The best yield for each strain was as follows: RTA strain in a media containing molase (8% v/v glucose equivalent) produced 61,79% w/w of B-glucan; RN4 strain in a media containing molase (1% v/v glucose equivalent) produced 98,42% w/w of B-glucan; SC strain in a media containing molase (2% v/v glucose equivalent) produced 56,48% w/w of B-glucan. One-way Anova followed by the Tukey-Bonferroni test indicated that molase can be used as substitute of glucose source in the YPG fermentation media, and significantly increased the B-glucan yield by all the three strains of Saccharomyces cerevisiae, as well as reducing the protein contents. The highest ß-glucan yield (98,42% w/w) was attained by the RN4 strain in a media containing molase (1% v/v glucose equivalent) with a protein impurity of only 10,53% w/w, while the RN4 and RTA strains produced a higher B-glucan yield than that of the SC strain.